Community Structure of Terrestrial Gastropods Based on Elevation in the Kabawetan Tea Plantation, Bengkulu, Indonesia - Darmi; Rizwar; Utari, Titi (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2024)
Terrestrial gastropods are a group of soil biota that function as herbivores, detritivores, and predators, with their presence contributing to the balance of soil ecosystems, including agroecosystems. This study aims to analyze the community structure of terrestrial gastropods based on elevation at the Kabawetan Tea Plantation, Kepahiang Regency, Bengkulu Province. Observation stations were determined using the stratified sampling method, consisting of locations at elevations of 800, 900, and 1000 meters above sea level (m asl). Sample collection was conducted using the horizontal line transect method along a 100-meter transect at each research location, with 20 plots of 50 cm × 50 cm along each transect, spaced 5 m apart. The spesies of terrestrial gastropods in the Kabawetan Tea Plantation comprised four species belonging to four families: Achatinidae (Achatina fulica), Subulinidae (Allopeas gracile), Camaenidae (Bradybaena sp.), and Ariophantidae (Parmarion martensi). Based on elevation, different species of terrestrial gastropods were found; at elevations of 800 and 900 m asl, two common species were identified, namely Achatina fulica and Bradybaena sp., while at 1000 m asl, three species were found, namely: Allopeas gracile, Bradybaena sp., and Parmarion martensi. The highest density of terrestrial gastropods wasrecorded at 1000 m asl. The species Bradybaena sp. consistently exhibited the highest abundance across all three research locations. The diversity of terrestrial gastropods at the three elevation strata in the Kabawetan Tea Plantation was classified as low (H′ < 1), and their distribution followed a cluster pattern.